Paravertebral Well-Differentiated Liposarcoma with Low-Grade Osteosarcomatous Component: Case Report with 11-Year Follow-Up, Radiological, Pathological, and Genetic Data, and Literature Review - Nicolas Macagno; Stéphane Fuentes; Gonzague de Pinieux; André Maues de Paula; Sébastien Salas; Jean-Camille Mattéi; Charlotte Dupuis; Romain Appay; Alain Aurias; Henry Dufour; Dominique Figarella-Branger; Corinne Bouvier (Case Reports in Pathology)
Despite being one of the most frequent soft-tissue sarcomas, well-differentiated liposarcoma has never been reported near the spine. The authors present the case of a 67-year-old man with progressive history of back pain. Physical examination revealed a mass located within the right paravertebral muscles. MR and CT imaging showed a heavily ossified central mass surrounded by a peripheral fatty component. No connection with the underlying bone was detected on imagery and during surgery. After surgical resection, histopathological examination revealed a tumor harboring combined features of well-differentiated liposarcoma and low-grade osteosarcoma. Tumor cells displayed overexpression of MDM2, CDK4, and P16 by immunohistochemistry and CGH revealed amplification of 12q13-15 as the only genetic imbalance. MDM2 FISH analysis was performed but was inconclusive. The pathological, immunohistochemical, and genetic features, the differential diagnoses, and the therapeutic management of this unusual tumor are discussed. No complementary treatment was performed initially. Following first treatment, two recurrences occurred 6 and 9 years later, both displaying histological features similar to the first occurrence. Radiotherapy was started after the second recurrence. Follow-up shows no evidence of disease 11 years after initial diagnosis. This case was unusual due to the paravertebral location of the tumor and its divergent differentiation.